2016
DOI: 10.1186/s12981-016-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and its effect on treatment outcome among HIV infected clients receiving HAART in Ethiopia: a cohort study

Abstract: PurposesThe aim of this study was to determine the effects of nutritional status at the start of highly active anti-retroviral therapy on treatment outcomes among HIV/AIDS patients taking HAART at Jimma University Specialized Hospital.MethodsWe performed a retrospective cohort study involving 340 adults who started highly active anti-retroviral therapy. The patients have been clinically followed for 2 years. Data were extracted from paper based medical charts by trained data collectors from January 30 to Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Studies also found that malnutrition was associated with lower CD4 count [ 5 ], and it tends to decrease CD4 counts recovery and predisposes patients to early death [ 35 ]. It was supported by the finding that micronutrient supplements significantly increased CD4 count among PLWHA [ 36 ].…”
Section: Discussionmentioning
confidence: 94%
“…Studies also found that malnutrition was associated with lower CD4 count [ 5 ], and it tends to decrease CD4 counts recovery and predisposes patients to early death [ 35 ]. It was supported by the finding that micronutrient supplements significantly increased CD4 count among PLWHA [ 36 ].…”
Section: Discussionmentioning
confidence: 94%
“…Tanzania is no exception. With such magnitudes of undernutrition, HIVpositive individuals are likely to succumb to treatment failure, higher risk of opportunistic infections [15,16], and even mortality [11,12,17]. Addressing undernutrition among adults is of paramount importance to attain treatment goals, especially in the new era of test and treat for all HIV-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…More than half had detectable viral loads (54.0%), and were under HAART (58.0%). The mean duration (in months) since HAART initiation was 7.8 months (± 4.5; range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and six patients (11.8%) were on a single tablet regimen. HIV diagnosis took place in 2015 for most patients (68.6%).…”
Section: Study Sample Characteristics: Sociodemographic and Clinical mentioning
confidence: 99%
“…QoL is influenced by "physical health, psychological state, level of independence, social relationships, personal beliefs and their relationship to salient features of their environment", according to the World Health Organization (WHO) (3). A better QoL has been observed in healthy populations compared to patients with chronic diseases (4,5). The relationship between nutrition, QoL and immune dysfunction, such as that seen in HIV, is interconnected (1); the disease progression is associated with a decline in nutritional status and immune function, even during highly active antiretroviral therapy (HAART) (6).…”
Section: Introductionmentioning
confidence: 99%